The role of registered nurses in primary care and public health collaboration: A scoping review - Monica Swanson; Sabrina T. Wong; Ruth Martin‐Misener; Annette J. Browne (Wiley, 2020)
Abstract Aim The purpose of this work was to examine the roles of Registered Nurses (RNs) in primary care (PC) and public health (PH) collaboration. Additionally, we aimed to explore whether the current scope of practice for RNs is adequate to support their roles in PC/PH collaboration. Design A scoping review of current literature relating to the RN's role in PC/PH collaboration was conducted using the PRISMA 2009 checklist. Methods The review used key terms: primary care, public health, collaboration, nursing and nurse role across six electronic databases; 23 articles that were included in the final review were published over a 7‐year span. Results Four key RN roles relating to PC/PH collaboration were identified: relationship builder, outreach professional, programme facilitator and care coordinator. RNs supported transitions in chronic disease, communicable disease care and maternity care at various healthcare system levels including systemic, organizational, intrapersonal and interpersonal levels.